Molecular analysis of sugar transporters and glycolysis pathways in Ettlia sp. under heterotrophy using fructose and glucose. Issue 1 (21st November 2021) - Kim, Minsik; Jeon, Seungjib; Kang, Nam Kyu; Lee, Hyung‐Gwan; Shin, Won‐Sub; Koh, Hyun Gi; Yun, Jin‐Ho; Ahn, Chi‐Yong; Oh, Hee‐Mock; Chang, Yong Keun
Abstract: Fructophilic behavior in microalgae is a rare trait that could benefit biorefineries by enabling substitution of carbon source with fructose, and our previous study identified that Ettlia sp. prefers fructose relative to glucose. In this study, by analyzing the transcription levels of genes related to sugar transport and the glycolysis pathway, the fructose utilization of Ettlia sp. was investigated. In a fructose‐containing medium, the expression levels of fructokinase (EttFRK3) and glucokinase (EttGCK1 and EttGCK2) genes were significantly upregulated in heterotrophic cultivation of Ettlia sp. under fructose supplementation conditions. Further, a sugar transporter ( EttSTF11 ) was significantly upregulated by 3.2‐fold in 1 day, and this increase was analogous to the specific growth rate exhibited by the species. Subsequent cultivation tests with multi‐sugar sources also showed a significant upregulation of EttSTF11 relative to other treatments without fructose. A phylogenetic tree derived from the analysis of different transporters of interest identified that EttSTF11 was adjacent to reference fructose transporters with a high bootstrap value of 71. Given that the transmembrane domains of EttSTF11 were analogous to those of reference fructose transporter genes, EttSTF11 appeared to play a critical role in fructose consumption and metabolism in Ettlia sp. Graphical Abstract and Lay Summary: In this study, we investigated the fructophilic behavior of Ettlia sp. Analyses on genes related to fructose transport and glycolysis elucidated the mechanism of fructose consumption of Ettlia sp. Notably, the fructose transporter (EttSTF11) and upregulated glycolysis genes by fructose are the main factors of the fructophilc growth.